Dietary Montmorillonite Improves the Intestinal Mucosal Barrier and Optimizes the Intestinal Microbial Community of Weaned Piglets - Liu, Han; Wang, Congmin; Gu, Xueling; Zhao, Jing; Nie, Cunxi; Zhang, Wenju; Ma, Xi (Frontiers in Microbiology, 2020)
The study investigated the impact of dietary montmorillonite on growth performance, intestinal mucosal barrier and microbial community in weaned piglets with control group (CON) and dietary supplementation of 0.2% montmorillonite (0.2% M). There is a tendency to increase the average daily gain (ADG) during days 15-35 and 1-35 and average daily feed intake (ADFI) during days 1-35 by adding the 0.2% M to the diets than the CON group (0.05 < P < 0.1). Besides, the higher villus height of duodenum and jejunum and the lower crypt depth of duodenum and colon in the 0.2% M group were revealed than that in the CON group, respectively (P < 0.05). Moreover, the V/C (ratio of the villus height and crypt depth) in the 0.2% M group was increased compared with that in the CON group both from duodenum and ileum (P < 0.05). The relative mRNA expression of mucin-1, ITGB1 (β1-integrins), PKC (protein kinase C) of ileum in the 0.2% M group were up-regulated (P < 0.05) compared to that in the CON group. The digesta sample of ileum from piglets in the 0.2% M group contained greater (P < 0.05) intestinal bacterial diversity and abundances of probiotics, such as Streptococcus, Eubacterium_rectale_group and Lactobacillus, which could promote the synthesis of carbon-containing biomolecules. Overall, dietary supplementation of 0.2% M have a tendency to improve the growth performance on weaned piglets and may enhance the intestinal mucosal barrier function via altering the gut microbiota.